Alternatively spliced isoforms of tissue factor pathway inhibitor - Maroney, S.; Ellery, Paul; Mast, A. (Pergamon, 2010)
Tissue factor pathway inhibitor (TFPI) is the major regulator of tissue factor (TF)-induced coagulation. It down regulates coagulation by binding to the TF/fVIIa complex in a fXa dependent manner. It is predominantly produced by microvascular endothelial cells, though it is also found in platelets, monocytes, smooth muscle cells, and plasma. Its physiological importance is demonstrated by the embryonic lethality observed in TFPI knockout mice and by the increase in thrombotic burden that occurs when heterozygous TFPI mice are bred with mice carrying genetic risk factors for thrombotic disease, such as factor V Leiden. Multiple TFPI isoforms, termed TFPIa, TFPIß, and TFPId in humans and TFPIa, TFPIß, and TFPI? in mice, have been described, which differ in their domain structure and method for cell surface attachment. A significant functional difference between these isoforms has yet to be described in vivo. Both human and mouse tissues produce, on average, approximately 10 times more TFPIa message when compared to that of TFPIß. Consistent with this finding, several lines of evidence suggest that TFPIa is the predominant protein isoform in humans. In contrast, recent work from our laboratory demonstrates that TFPIß is the major protein isoform produced in adult mice, suggesting that TFPI isoform production is translationally regulated. © 2010 Elsevier Ltd. All rights reserved.